APPLICATION OF MULTITEMPORAL LANDSAT DATA IN MAPPING OF SALINE SOIL IN KANO RIVER IRRIGATION SCHEME (KRIS) - Mohammed, Dahiru; Maina, M. M.; Audu, I.; Tudunwada, I. Y.; Nasiru, N. K.; Nasidi, N. M.; Umar, S. E. (FUDMA JOURNAL OF SCIENCES, 2023)
Soil salinization is becoming a more serious issue threatening agricultural production and the sustainable use of land resources. Crop roots are unable to absorb water from the soil when exposed to saline conditions. This study explored the potential of Landsat imagery in detecting and mapping saline soil in the Kano River Irrigation Scheme (KRIS).  Samples of soil were collected from thirty-nine (39) sectors of the KRIS for ground truthing on 20th – 25th April, 2020. Electrical Conductivity (EC) of field samples were correlated with band values of satellite images and salinity indices in order to determine their relationship and assess their effectiveness in predicting soil salinity. Using a geospatial approach, the data was analyzed and maps of salt-affected areas were generated. ArcGIS 10.6 was used as the primary package for modeling and running functions. The result has shown that the EC values over the entire study area are greater than 1.3 dS/m. However, the mean value of EC is approximately 1.91 dS/m. The implication is that, most of the vegetables such as Onion, Carrot, and Beans grown in the KRIS will experience yield reduction without appropriate management practice as their threshold value has been exceeded.
Keywords: Irrigation; Landsat; Mapping; Saline; Soil